Novel phthalide derivatives identified from Ligusticum chuanxiong (Chuanxiong). Issue 1 (December 2016) - Yang, Jun; Feng, Xiao-Lin; Yu, Yang; Wang, Qi; Zou, Jian; Wang, Chuan-Xi; Mu, Zhen-Qiang; Yao, Xin-Sheng; Gao, Hao
Abstract Background Ligusticum chuanxiong Hort. (Chuanxiong ) is a well-known Chinese medicine, and studies on its chemical constituents are important for explaining its mechanism of action and quality control. This study aims to investigate the chemical constituents of the dried rhizome of.L. chuanxiong. Methods The dried rhizome ofL. chuanxiong was extracted with 60 % ethanol, and the concentrated extract was isolated by silica gel, octadecyl silane, and Sephadex LH-20 columns, followed by preparative/semipreparative high-performance liquid chromatography (HPLC) to obtain the pure chemical constituents. The structures of the constituents were elucidated by HR-ESI-MS, UV, IR, 1D NMR, and 2D NMR methods. Enantiomeric separation was achieved by a chiral HPLC method. The absolute configuration was determined by the modified Mosher's method. Results Six novel phthalide derivatives, (+)/(−)-chuanxiongins A–F (1 –6 ), together with four known phthalides (7 –10 ) were isolated fromChuanxiong . All of the new compounds (1 –6) were present as pairs of enantiomers. Enantiomeric separation of1 was successfully achieved by HPLC on a chiral column. The absolute configuration of (−)-1 was determined by a modified Mosher's method. Conclusion The six novel phthalide derivatives (1 –6 ) isolated fromChuanxiong were phthalide fatty acid esters that were structurally analogous and characterized by fatty acid acylation at 6-OH or 7-OH.